Uso de inseticidas organofosforados nos pólos de produção na Ilha de São Luis — MA: condições de trabalho e contaminação de hortaliças - Araújo, Soraya Maria Mendonça (2000)
The present research aimed to evaluate the way of utilization and the vegetables contamination leveis by organophosphates insecticides having as active ingredient methamidophos and parathion-methyl, apllied regularly on the crops of tomato (Lycopersicum esculentum MilL), green pepper (Capsicum annum, L.), kale (Brassica oleracea L.) and coriander (Çoriandrum sativum L.), produced and commercialized at São Luis Island, State of Maranhão, Brazil. In the first step of research, it was applied a questionary at the production poles, located in São Luis, Paço do Lumiar, Raposa and São José de Ribamar counties, regarding informations about the technologic profile of horticulturists and the process of agrochemical utilization. The second stage consisted in a random collect of four vegetables from six production poles of fourteen interviewed. The collects were taken in free fair of Cohab, being the samples formed of 500g tomato and green pepper, and four packets of kale and coriander, with four replications per vegetable, totaled 16 samples. After collecting, vegetable samples were taken to the Universidade Federal do Maranhão for the cbromatographic extract preparation, while the chromatographic analysis were performed at the Universidade Federal de Viçosa. According obtained residts, it was verified that: interviewed horticulturists have not been receiving any type of technical official support; they use regularly several agrochemicals to pest control, with prevalence of Tamaron BR and Folidol 600; in the most of production poles, the insecticides are applied of inadequate way, regarding recommended dose in labei of product, application gap, utilization ofprotection and safety equipmenfs and discard of packings; samples of tomato, green pepper and coriander presented médium leveis of methamidophos residues around 0.041, 0.113 and O.OSlmg.Kg"1, in this order, and that none of the analyzed vegetable samples showed to have residues of parathion-methyl insecticide. It could be concluded that, among the main causes of pesticide contamination in foodstuffs, the lack of basic information of the farmers is the major problem